ANALISIS PEMAHAMAN KONSEP DAN KESULITAN SISWA KELAS VII PADA MATERI BILANGAN BULAT - Shofura Zahroh; Sri Yunita Ningsih (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to analyze the mathematical conceptual understanding of seventh-grade students on the topic of integers and to identify the difficulties experienced by students in solving problems. This study employed a qualitative method with a descriptive approach. The research subjects were 23 students of class VII-3 at SMP Negeri 2 Pasir Penyu in the 2025/2026 academic year. The research instruments used were a conceptual understanding ability test and interviews. The results showed that the mathematical conceptual understanding ability of class VII-3 students was still relatively low. This can be seen from the highest number of students being in the low category, consisting of 10 students; 3 students in the very low category; 3 students in the moderate category; 5 students in the high category; and 2 students in the very high category. In general, students were able to understand basic concepts, but they still experienced difficulties in analyzing and applying mathematical concepts. The low ability was presumably caused by a less engaging learning process. Therefore, more innovative learning approaches are needed, such as the demonstration method and PMRI, as well as contextual problems related to daily life so that mathematics learning becomes more meaningful and enjoyable.Keywords: Conceptual Understanding, Learning Difficulties, Junior High School